Anatomy of the sural nerve in a computer-assisted model: implications for surgical minimal-invasive Achilles tendon repair. Issue 7 (8th March 2007) - Citak, Musa; Knobloch, Karsten; Albrecht, Knut; Krettek, Christian; Hufner, Tobias
Abstract : Background: Sural nerve injuries are an evident risk especially of minimal-invasive surgical Achilles tendon repair. However, detailed anatomical studies focusing on the relationship of the sural nerve with the Achilles tendon at various levels are scarce, even pending in two planes. Aim: To determine the position and course of the sural nerve in relation to the Achilles tendon in two planes after trans-section and computer-assisted determination. Methods: The exact course of the sural nerve was determined in 10 cadavers (55.3 years, 19–89 years), using a computer-assisted method in two planes (transversal/sagittal). Results: The sural nerve crossed the Achilles tendon at 11 (8.7–12.4) cm proximal to the tuber calcanei. The distance between the lateral crossing and the proximal musculotendineus junction was 35 (20–58) mm. Starting from the tuber calcanei, the distance was 2/2 mm (transversal/sagittal plane) at 11 cm proximal to the tuber calcanei, 4/4 mm at 10 cm proximal, 5/6 mm at 9 cm, 8/10 mm at 5 cm and 11/18 mm at the tuber calcanei. Conclusion: In the lateral crossing region of the sural nerve and the lateral proximal Achilles tendon 9–12 cm proximal to the tuber calcanei, a close relationship of both anatomical structures can be visualised using computer-assisted measurements; caution is suggested to prevent sural nerve entrapment in either open or percutaneous Achilles tendon repair.